Default Interest in Public Procurement Contracts: Between Statute and Practice – A Study Based on Recent Legislative Reforms – - Haffar, Chafia; Rahal, Sihem (Journal of Legal Studies and Researches, 2026)
Public procurement contracts grant the public purchaser exceptional powers, including unilateral termination and financial penalties. In return, the co-contractor is entitled to delay interests for late payments, as mandated by public accounting laws and regulations. This study examines the legal basis and practical enforcement of such interests in light of recent legislative reforms.